2013 IEEE International Symposium on Information Theory 2013
DOI: 10.1109/isit.2013.6620614
|View full text |Cite
|
Sign up to set email alerts
|

Optimal channel switching in the presence of stochastic signaling

Abstract: Abstract-Optimal channel switching and detector design is studied for M -ary communication systems in the presence of stochastic signaling, which facilitates randomization of signal values transmitted for each information symbol. Considering the presence of multiple additive noise channels (which can have nonGaussian distributions in general) between a transmitter and a receiver, the joint optimization of the channel switching (timesharing) strategy, stochastic signals, and detectors is performed in order to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 14 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…In practice, this assumption can be realized by employing a communication protocol that allocates the first N s,1 symbols in the payload for channel 1, the next N s,2 symbols in the payload for channel 2, and so on. The information on the number of symbols for different channels can be included in the header of a communications packet [10,19].…”
Section: Optimal Channel Switchingmentioning
confidence: 99%
See 3 more Smart Citations
“…In practice, this assumption can be realized by employing a communication protocol that allocates the first N s,1 symbols in the payload for channel 1, the next N s,2 symbols in the payload for channel 2, and so on. The information on the number of symbols for different channels can be included in the header of a communications packet [10,19].…”
Section: Optimal Channel Switchingmentioning
confidence: 99%
“…In the presence of multiple channels between a transmitter and a receiver, it may be advantageous to perform channel switching; that is, to transmit over one channel for a certain fraction of time, and then switch to another channel during the next transmission period even if the channel statistics are not varying with time [6,17,18,19]. In [6], it is shown that the optimum performance under an average power constraint can be achieved by time sharing between no more than two channels and power levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent conference paper [28], we have presented the optimal channel switching, signaling and detection problem, and provided its solution. The current paper presents a more detailed derivation of this solution.…”
Section: Introductionmentioning
confidence: 99%